Matrix metalloproteinase-8 levels in oral samples as a biomarker for periodontitis in the Chinese population: an observational study - Chao Yuan; Xiaochen Liu; Shuguo Zheng (BMC, 2018)
Abstract Background Clinical evaluation of periodontal inflammation does not fully reflect the disease activity. Extensive studies have been conducted out on gingival crevicular fluid (GCF) components that might serve as potential diagnostic markers for periodontitis, among which matrix metalloproteinase-8 (MMP-8) has shown to be promising, but there were no studies for individuals in China. The aim of this study was to compare clinical diagnostic parameters and levels of active MMP-8 (aMMP-8) in GCF and oral rinse samples from the Chinese patients with varying degrees of periodontal inflammation. Methods GCF and oral rinse samples were obtained from 60 participants into two groups, a periodontitis group and a control group, specified by the presence and number of pocket depths or attachment loss. The aMMP-8 levels in GCF and oral rinse samples was quantified by ELISA using specific monoclonal antibodies. Logistic and linear regression models were employed for testing the correlation between aMMP-8 levels and periodontal condition, as well as diagnostic sensitivity and specificity. Results Periodontitis group (mean = 24.84 ng/ml) exhibited significantly higher aMMP-8 levels than control group in GCF (p < 0.001). The aMMP-8 levels in oral rinse samples ranged from 0.05 to 2.18 ng/ml, but differences were not statistically significant between the two groups (p > 0.1). Receiver operating characteristic curve analysis showed a highest threshold of 6.66, with a corresponding sensitivity and specificity of 0.8 and 0.9, respectively. Conclusions Measuring aMMP-8 levels in GCF may have potentiality for complementary early diagnosis of periodontal disease and inflammation in the Chinese population.